The effect of using flashcards on vocabulary mastery of elementary students - Yayu Sri Rahayu; Enung Rostika (Journal of Research in English Language Teaching and Linguistics, 2025)
Vocabulary acquisition is fundamental to early language learning, playing a critical role in the development of communication skills among elementary students. While flashcards have been widely recognized for enhancing vocabulary learning, most existing research focuses on digital flashcards used by older learners, leaving a gap in empirical studies targeting the effectiveness of printed flashcards in primary classrooms. This study aims to examine the impact of using traditional flashcards on the vocabulary mastery of elementary students. Adopting a quantitative research design, the study involved a group of elementary students divided into experimental and control groups. The experimental group received vocabulary instruction using flashcards, while the control group followed conventional methods. Data were collected through pre-tests and post-tests to measure vocabulary mastery. The results were analyzed using statistical methods to assess differences between the two groups. Findings reveal that students taught using flashcards showed a significant improvement in vocabulary mastery compared to those in the control group. This suggests that flashcards serve as an effective visual aid in reinforcing word recall and retention among young learners. The implications of this study underscore the value of incorporating simple, tangible learning tools like flashcards into classroom instruction, especially in settings where digital resources are limited. These findings contribute to the development of effective vocabulary teaching strategies in early language education and support the integration of visual learning tools that align with the cognitive needs of young learners.